SOSIALISASI PEMBUATAN HAND SANITIZER EKSTRAK LIDAH BUAYA DI DESA BUNUT WETAN KECAMATAN PAKIS - Hanjar Ikrima Nanda; Nanda Trisnawan; Inka Prananda Putri; Adhitya Dwi Permana (Jurnal Abdimas Bina Bangsa, 2021)
During the pandemic, preventive measures are needed to avoid the transmission of the Corona virus. One of these actions is the use of hand sanitizers to maintain hand hygiene. The Malang State University Community Service Team held a socialization on the manufacture of aloe vera extract hand sanitizer. The purpose of this activity is to provide education and training on making hand sanitizers from natural ingredients. Hand sanitizers made from natural ingredients are relatively inexpensive and easy to obtain. The activity stages are interviews related to problems that exist in Bunut Wetan Village, then discussions and permits to the village. The socialization was carried out to posyandu cadres starting with the presentation of the material, followed by the practice of making aloe vera extract hand sanitizer and filling out questionnaires. Based on the results of the questionnaire, 95.83% of respondents understood that hand sanitizers can be made from natural ingredients, 88.54% understood the benefits of aloe vera in making hand sanitizers, the function of the ingredients for making hand sanitizers and how to make hand sanitizers with aloe vera extract, 90.63% Posyandu cadres understand the benefits of hand sanitizers